Optimization of Germination Process of Isothiocyanate Enrichment in Broccoli Sprouts by Response Surface Methodology - Minglang GU; Yingqi GUO; Yongqi YIN; Xudong HE (Shipin gongye ke-ji, 2022)
The accumulation of isothiocyanate in germinated broccoli under ZnSO4-melatonin treatment was optimized. The isothiocyanate content, bud length and fresh weight of broccoli during germination were used as indices to study the effects of germination temperature, germination time, ZnSO4 and melatonin treatment concentration on isothiocyanate by single factor experiment first, and on this basis, it was further optimized by response surface experiment. Meanwhile, the changes of isothiocyanate metabolism related indexes were analyzed. The results showed that germination temperature, germination time, ZnSO4 and melatonin treatment concentration all had significant effects on isothiocyanate enrichment. Response surface optimization experiment showed that when the broccoli was treated with 4.69 mmol/L ZnSO4 combined with 13.18 μmol/L melatonin at 30 ℃ for 3 days, the isothiocyanate content was up to the highest, which was 451.27 mg/100 g mf. The contents of glucosinolates and sulforapenin and the activity of myrosinase in broccoli sprouts under ZnSO4 combined with melatonin treatment were significantly higher than those in the control group(P<0.05). This study showed that ZnSO4-melatonin treatment was an effective means to enrich isothiocyanate in broccoli sprouts. The optimized germination process can provide technical support for the production of broccoli sprouts rich in isothiocyanate.